Strategi Penentuan Harga Jasa Pendidikan - Ishlah Farah Diba; Abdul Mu’in Bahaf (Epsilon Journal of Management, 2024)
The strategy for determining the price of educational services is a plan or approach used by an educational institution to determine the price of the educational services they offer to students. This research method uses the literature research method, namely a literature study approach to search for and collect literature related to strategies for determining the price of educational services. The focus of this article is1) Basic Strategy for Determining Prices for Educational Services, 2) Targets of the Strategy for Pricing Educational Services, 3) Techniques for Determining Prices for Educational Services, and 4) Pricing Model for Educational Services. The main determining factor in determining prices is the objectives of an educational institution. These goals can be in the form of maximizing profits, maintaining the continuity of education, achieving a large market share, creating leadership in terms of quality, overcoming competition, and carrying out social responsibility.